Fitur Bahasa Wanita Menteri Kang Kyung Hwa Pada Kuliah Umum “Hanbando Jongsewa Gellobol Wegyo” (한반도 정세와 글로벌 외교) - Dwina Rahmaniar Hapsari (Madah: Jurnal Bahasa dan Sastra, 2022)
This qualitative descriptive study identifies and analyzes the language features of women based on the Lakoff theory by Kang Kyung Hwa in the public lecture “Hanbando Jongsewa Gellobol Wegyo” (한반도 정세와 글로벌 외교). The data collection technique uses listening and note-taking techniques and the data analysis techniques uses data collection, data reduction, data presentation and conclusions. The results of the study found that 9 out of 10 women's language features is found on this study with lexical hedges or fillers features being the most found because Kang expresses her confidence and conveys her certainty about something and in order to avoid mistakes when making statements, the precise color terms feature is not found in this study because it is not related to the topic of discussion.